Challenges during commissioning and operation in photovoltaic power plants by electrical faults - SAĞLAM, ŞAFAK; ORAL, BÜLENT (My University, 2023)
Problems such as increasing environmental pollution and global warming due to fossil fuels used in energy production have revealed the requirement for renewable energy sources. In addition to this situation, the decreasing fossil fuel reserves, and the need to diversify energy production resources to ensure energy supply security for countries have made the use of renewable energy sources a necessity. Therefore, demand for solar energy will continue to increase, considering the increasing renewable energy need. To increase energy efficiency, the uninterrupted production of photovoltaic power plants during production hours is important to reduce the consumption of fossil fuels. For this reason, situations and malfunctions that prevent uninterrupted operations should be detected. Fault classification contributes to the rapid identification of problems by providing fast diagnostics for possible faults. When the previous studies in this field are examined, there are publications about general faults in photovoltaic power plants and publications about electrical faults separately. However, there are limitations in academic studies that deal with the difficulties encountered in the commissioning and operation of photovoltaic power plants in detail and examine electrical faults. In this context, there is a need for relevant studies. In this study, the possible failures that may occur during the commissioning and operation of photovoltaic power plants will be categorized and this study is intended to be a resource for studies on this subject. It is aimed to create a resource for academic studies and to contribute to field applications to companies in the sector.
Keywords: Commissioning; Failure; Fault classification; Operation; Photovoltaic